Strengthening Female Students’ Character through Islamic Religious Education in the Digital Era - Salma Fuji A (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) in strengthening the character of ninth-grade female students (santriwati) at SMP Islam Sabilul Wafa in the digital era. The background of this research is based on the rapid development of information technology, which brings both positive impacts and challenges to students' character formation, particularly in moral and religious aspects. This study employed a qualitative approach with a case study design. The research subjects consisted of five female students selected through purposive sampling. Data were collected through in-depth interviews and observation, while data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing. The results indicate that PAI plays a significant role in strengthening students' character, especially in terms of religiosity, discipline, and responsibility. In the digital era, PAI also functions as a moral foundation that helps students filter information and use technology wisely. Supporting factors include a religious school environment and the role of teachers as role models, while inhibiting factors come from technological influences and external environments.